Structure, composition and economic potential of molluscs (gastropods and bivalves) in the Lembupurwo Lagoon Beach, Kebumen, Central Java, Indonesia - Rohman, Cahya Maulidta; Kinanti, Asih; Pramudita, Desma Asty; Fadzilah, Fariz Pradana Adil; Ramadhan, Muhammad Fadhil; Faturrahman, Aqra Danial; Aurina, Devi Mayang; Dewi, Mini Ambarwati Kusuma; Ainaya, Fadia Aulianissa; Rachmalia, Fayza; Fatikha, Layyinatssyifa A’yuni; Nugroho, Gilang Dwi; Yap, Chee Kong; Setyawan, Ahmad Dwi (Genbinesia Journal of Biology, 2023)
The mangrove ecosystem is a productive ecosystem with economic and environmental functions. This research was conducted to determine the value of the ecological index and the economic potential of molluscs (Gastropods and Bivalvia) found in the Lembupurwo Lagoon Beach (part of Wawar River Estuary), Kebumen District, Central Java, Indonesia. First, mollusc sampling was carried out on a 10x10 meter plot. So its existence also needs to be known and studied more specifically. Then, the ecological index of the species found is calculated using the Shannon-Wiener Diversity Index, Evenness Index, Simpson Dominance Index, Margalef Species Richness Index, and individual Density of each species. In addition, for the economic potential of molluscs using secondary data from scientific journals. Analysis of the data obtained descriptively with the support of tables and pictures. The study results showed that there were 17 species of molluscs consisting of 12 species belonging to the gastropod class and five other species belonging to the bivalves. The families with the most common species are Neritidae=3, Ellobiidae=2, and Littorinidae=2. Whereas in the Bivalvia class, each family was only found one species. The total molluscs found had a density value of 3.95 ind/m2. The Diversity Index (H') of molluscs was 1.48 (moderate), Evenness Index was 0.52 (moderate), Margalef Richness Index was 1.71 (low), and Dominance Index was 0.28 (no species dominated). Then, for the economic potential of the mollusks found, the economic potential is dominated by the food sector. The species that have potential in the food sector include: Faunus ater Linnaeus 1758, Isognomon ephippium Linnaeus 1758, Pilsbryoconcha exilis I.Lea, 1838, Polymesoda expansa Mousson 1849, and Anadara antiquata Linnaeus 1758.